Impactos macroeconômicos do choque fiscal de 2015: A regularizaç\~ao de despesas públicas n\~ao contabilizadas - Marco Antônio Freitas de Hollanda Cavalcanti; Luciano Vereda Oliveira; Rafael Zanderer; Matheus Rabelo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This paper analyzes the macroeconomic impacts derived from the recognition of previously unreported fiscal liabilities during 2015 in Brazil. This is done within a DSGE model with a detailed public sector developed and calibrated for the Brazilian economy. The gradual recognition of these fiscal liabilities is interpreted as a series of "news shocks" in response to which private agents may have updated their expectations regarding the sustainability of the public debt and the implementation of fiscal adjustment measures, thus generating potentially significant macroeconomic effects. The paper's main results are: i) the shocks related to the recognition of previously unreported fiscal liabilities may have caused significant output loss and inflationary pressure; ii) a fiscal reaction function based on the reduction of public employment and the increase in income tax rates would have generated smaller macroeconomic costs relative to the rule actually adopted (based on the reduction of public consumption and investment); iii) delaying or downsizing the required fiscal adjustment in the short run would have led to the worsening of fiscal indicators and generated much larger costs in terms of output loss and higher inflation.
Keywords: E17; E37; E62; E65; 330; DSGE models; fiscal policy; fiscal transparency